Dampak Covid-19 terhadap Pariwisata Sumatra (Journal of Regional and Rural Development Planning (Jurnal Perencanaan Pembangunan Wilayah dan Perdesaan), 2022)
This paper discusses the impact of the Covid-19 pandemic which has paralyzed tourism, especially in Sumatra. Unlike the previous crises, the Covid-19 impact is wider and bigger. The closure of transportation access and advice to stay at home made the tourism sector sluggish. Sumatra is one of the areas that has been hit quite hard due to the pandemic. Areas that experience deeper contraction need to be prioritized for tourism recovery as soon as possible. This study uses quantitative research methods to find theoretical references in various scientific journals, books, reports, and actual and trusted news on the internet that are relevant to cases or problems. This study aims to see how much influence the pandemic has on tourism in Sumatra and identify which provinces should be the top priority in accelerating recovery. The main comparison variable used is the hotel room occupancy rate of each province. From the analysis of the odds ratio, it is concluded that tourism in the provinces of Sumatra is more vulnerable to the impact of the pandemic than in other regions in Indonesia. Areas with archipelagic topography such as Riau, Riau Islands and Bangka Belitung were identified as the areas hit hardest by the pandemic.